Alpha- and beta-melanocyte stimulating hormone positively impact lipogenesis of meibomian gland cells in vitro and ex vivo - Zahn, Ingrid; Socher, Eileen; Bergua, Antonio; Schikorra, Thilo; Kleinsasser, Benedikt; Garreis, Fabian; Schicht, Martin; Dietrich, Jana; Paulsen, Friedrich (Biomedicine & Pharmacotherapy, 2025)
Purpose The meibomian glands produce a lipid-rich secretion that forms the superficial layer of the tear film, preventing excessive evaporation. Dysfunction of these glands (MGD) is the primary cause of dry eye disease (DED), a growing public health concern. Currently, there are limited pharmacological treatments for DED. However, α-/β-melanocyte-stimulating hormones (α-/β-MSH), ligands of the melanocortin receptors (MCR), are known to regulate lipogenesis and differentiation in sebaceous glands. This study investigated the influence of α-/β-MSH on exocrine secretion in human meibomian glands. Methods Immunohistochemistry and RT-PCR for MCR expression were performed in human meibomian glands and an immortalized human meibomian gland epithelial cell line (ihMGECs). The effects of α-/β-MSH (agonists) and JNJ-10229570 (antagonist) in ihMGECs on lipid production and MCR response were analyzed using Oil-Red-O staining, transmission electron microscopy, qPCR, and a cAMP assay. Additionally, the effect of α-/β-MSH on an ex vivo organotypic slice culture (OSC) of human eyelids was investigated. Results MCR expression was confirmed in human meibomian glands. Stimulation with α-/β-MSH increased cAMP levels and MCR expression. α-/β-MSH dose-dependently induced lipid production in ihMGECs and OSC, resulting in increased lipid droplet formation and upregulation of lipogenesis markers. Co-administration of JNJ-10229570 suppressed this effect. Conclusion Our data show for the first time that human meibomian glands express MCRs and that stimulation/inhibition of MCRs alters cAMP response, MCR expression, and lipogenesis markers, thereby affecting the genesis of meibum. Therefore, α-/β-MSH positively impacts meibum production and should be considered in the context of changes in glandular secretion in MGD and potential treatment
Keywords: Dry eye disease; Meibomian gland; Meibomian gland dysfunction; Melanocortin receptor; Organotypic slice culture; α-MSH; β-MSH

Molecular detection of lacrimal apparatus and ocular surface - related ABC transporter genes - Kleinsasser, Benedikt; Garreis, Fabian; Musialik, Maximilian; Zahn, Ingrid; Kral, Barbara; Kutlu, Zeynep; Sahin, Afsun; Paulsen, Friedrich; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2024)
The ocular system is in constant interaction with the environment and with numerous pathogens. The ATP-binding cassette (ABC) transporters represent one of the largest groups among the transmembrane proteins. Their relevance has been demonstrated for their defense function against biotic and abiotic stress factors, for metabolic processes in tumors and for their importance in the development of resistance to drugs. The aim of this study was to analyze which ABC transporters are expressed at the ocular surface and in the human lacrimal apparatus. Using RT-PCR, all ABC transporters known to date in humans were examined in tissue samples from human cornea, conjunctiva, meibomian glands and lacrimal glands. The RT-PCR analyses revealed the presence of all ABC transporters in the samples examined, although the results for some of the 48 transporters known in human and analyzed were different in the various tissues. The present results provide information on the expression of ABC transporters at the mRNA level on the ocular surface and in the lacrimal system. Their detection forms the basis for follow-up studies at the protein level, which will provide more information about their physiological significance at the ocular surface and in the lacrimal system and which may explain pathological effects such as drug resistance.
CRIS-Team Scopus Importer:2024-05-17
Keywords: ABC transporter; Cornea; Eye; Lacrimal gland; Meibomian gland; Ocular surface

The Translational Role of MUC8 in Salivary Glands: A Potential Biomarker for Salivary Stone Disease? - Schicht, Martin; Reichle, Adrian; Schapher, Mirco; Garreis, Fabian; Kleinsasser, Benedikt; Aydin, Malik; Sahin, Afsun; Iro, Heinrich; Paulsen, Friedrich (Diagnostics, 2021)
Mucin (MUC) 8 has been shown to play an important role in respiratory disease and inflammatory responses. In the present study, we investigated the question of whether MUC8 is also produced and secreted by salivary glands and whether it may also play a role in the oral cavity in the context of inflammatory processes or in the context of salivary stone formation. Tissue samples from parotid and submandibular glands of body donors (n = 6, age range 63-88 years), as well as surgically removed salivary stones from patients (n = 38, age range 48-72 years) with parotid and submandibular stone disease were immunohistochemically analyzed targeting MUC8 and TNF alpha. The presence of MUC8 in salivary stones was additionally analyzed by dot blot analyses. Moreover, saliva samples from patients (n = 10, age range 51-72 years), who had a salivary stone of the submandibular gland on one side were compared with saliva samples from the other "healthy " side, which did not have a salivary stone, by ELISA. Positive MUC8 was detectable in the inter- and intralobular excretory ducts of both glands (parotid and submandibular). The glandular acini showed no reactivity. TNF alpha revealed comparable reactivity to MUC8 in the glandular excretory ducts and also did not react in glandular acini. Salivary stones demonstrated a characteristic distribution pattern of MUC8 that differed between parotid and submandibular salivary stones. The mean MUC8 concentration was 71.06 ng/mL in female and 33.21 ng/mL in male subjects (p = 0.156). Saliva from the side with salivary calculi contained significantly (15-fold) higher MUC8 concentration levels than saliva from the healthy side (p = 0.0005). MUC8 concentration in salivary stones varied from 4.59 ng/mL to 202.83 ng/mL. In females, the MUC8 concentration in salivary stones was significantly (2.3-fold) higher, with an average of 82.84 ng/mL compared to 25.27 ng/mL in male patients (p = 0.034). MUC8 is secreted in the excretory duct system of salivary glands and released into saliva. Importantly, MUC8 salivary concentrations vary greatly between individuals. In addition, the MUC8 concentration is gender-dependent (& FEMALE; > & MALE;). In the context of salivary stone diseases, MUC8 is highly secreted in saliva. The findings support a role for MUC8 in the context of inflammatory events and salivary stone formation. The findings allow conclusions on a gender-dependent component of MUC8.
CRIS-Team WoS Importer:2022-01-14